The transcription factors and pathways underpinning male reproductive development in Arabidopsis - Wiese, Anna Johanna; Torutaeva, Elnura; Honys, David (Frontiers in Plant Science, 2024)
As Arabidopsis flowers mature, specialized cells within the anthers undergo meiosis, leading to the production of haploid microspores that differentiate into mature pollen grains, each containing two sperm cells for double fertilization. During pollination, the pollen grains are dispersed from the anthers to the stigma for subsequent fertilization. Transcriptomic studies have identified a large number of genes expressed over the course of male reproductive development and subsequent functional characterization of some have revealed their involvement in floral meristem establishment, floral organ growth, sporogenesis, meiosis, microsporogenesis, and pollen maturation. These genes encode a plethora of proteins, ranging from transcriptional regulators to enzymes. This review will focus on the regulatory networks that control male reproductive development, starting from flower development and ending with anther dehiscence, with a focus on transcription factors and some of their notable target genes.